The Relevant Oral Burden of Patients with Hidradenitis Suppurativa - Giovanni Damiani; Pierpaolo Poli; Alessia Pacifico; Elia Rosi; Giovanni Allocca; Emilio Berti; Silvio Taschieri; Margherita Tumedei; Massimo del Fabbro; Santo R. Mercuri; Marino Bindi; Luca Francetti; et al. (Adis, Springer Healthcare, 2023)
Abstract Introduction Interleukin-17 plays a pivotal role in both hidradenitis suppurativa (HS) and in maintaining oral homeostasis, but their potential link remains unknown. Thus, we aimed to evaluate and quantify the oral burden of patients with HS. Methods In this real-life, multicenter, cross-sectional study, patients with HS were clinically evaluated by two board-certified dermatologists and two board-certified dentists. Oral comorbidities were carefully collected with medical history and therapeutic information. Results A total of 102 patients (44.0 ± 0.9 years, body mass index 27.0 ± 2.2 kg/m2) were enrolled. Remarkably, 48% and 43% did not undergo at least an oral hygiene or a dental visit each year, respectively. Oral disorders were found in 55.9% of patients with HS, in particular 39.2% had caries and 46.7% reported at least one missing tooth. The main oral manifestations in patients with HS were recurrent aphthous stomatitis (N = 19, 19.2%), amalgam tattoo (N = 14, 14.1%), leukoplakia (N = 11, 11.1%), nicotinic stomatitis (N = 9, 9.1%), papilloma (N = 8, 8.1%), and geographic tongue (N = 8, 8.1%). Whilst the main predictor of oral pathological conditions was Hurley staging (P = 0.0276), multivariate regression analysis indicated that gender and International Hidradenitis Suppurativa Severity Score System (IHS4) were the main predictors for the presence of caries and number of missing teeth. Conclusion As a result of the relevant oral burden in patients with HS, dentists should be part of the multidisciplinary team and oral education should be promoted among patients with HS.